Evaluation of the Malignancy Risk in Nodules Expanding the Thyroid Gland Capsule - Arslan, Ismail Emre; Bostan, Hayri; Hepşen, Sema; Akhanli, Pinar; Sencar, Muhammed Erkam; Cakal, Erman (Hormone and metabolic research, 2024)
There has been an increase in the diagnosis of thyroid nodules in recent years. In addition to the well-known criteria, features that are likely to increase the risk of malignancy are in the research process. In this study, we aimed to evaluate the malignant potential of nodules that expand the thyroid capsule ultrasonographically. A total of 109 patients with thyroid capsule-expanding nodules and 288 patients with non-expanding nodules were included in the study. Demographical data, ultrasonography features, and cytology results were noted, and histopathological findings were determined in operated patients. While malignant cytology was detected in 5.5% of capsule-expanding nodules in FNAB results, this rate was 0.7% in the non-capsule expanding group (p<0.001). According to the histopathological results, the incidence of malignancy was 15.6% in the capsule-expanding nodule group, while it was 3.1% in the other group (p=0.001). As a result of logistic regression analysis, it was determined that the risk of malignancy increased by 4.44-fold (95% CI 1.4-13.8, p=0.01) in patients with capsule-expanding nodules. Other features that increased the risk of malignancy were hypoechogenicity, microcalcification, and irregular margin presence. In this study, we found that the risk of malignancy increased in nodules expanding the thyroid capsule. Based on the increasing study data on this subject, monitoring thyroid capsule expansion in nodules may take its place among the criteria for malignancy in future evaluations.